Pienten elintarvikealan yritysten markkinointistrategiat - Kupiainen, Terri (Maatalouden taloudellinen tutkimuslaitos, 1996)
The subject of this research report was to discuss how marketing is implemented in small business firms. A great emphasis is laid on the factors that affect the entrepreneurs decision making especially in context of marketing strategy formulation and selecting of operations. The sensitising framework of resource-conditions-marketing-strategies-outcomes relationships was used as an interview quide. Data comprise 62 interviews collected from small food manufacturing firms using criterion sampling. The business of informants can be defined as small or very small, and there are part-timers too. About one half of the firms were situated in rural areas and one half in the metropolitan area in Finland. According to the results, one can hypothetisise that entrepreneurs goal setting in business is affected by their personal values and controlling objectives that frame entrepreneurs decision making. However, cost-benefit criteria are the most commonly used when evaluating the possible outcomes of different marketing functions and operations or marketing performance. Often the valuation is based on intuitive judgements and past experience, but in some cases also more exact calculations are used. The whole set of marketing strategic behaviour is also affected by learning and entrepreneurs possibilities to take up their marketing tasks internally or to use external marketing services. Even if the most established firms may have better resources, they often indicate less intention to make economic inputs in marketing because the cost-benefit relationships are perceived insufficient. In small firms the positioning to the competitive environment was mainly based on product ideas or market niches, and the segmentation- based strategies are not dominant. Sometimes the niche strategy equals to the certain segment, but in many cases the segment is not defined. The marketing strategies of the firms proved to be the combinations of product, different services and quality of operations as well as the mix of personal selling, relationship marketing and product demonstrations. Sometimes the public relationships are included too. The emphasis of each of these elements may depend on the firms target markets and selected marketing channels, but also the individual customers or clients of the firms exert their influence on marketing decisions. Competitive claims, which are partly parallel with the marketing strategic components, contain implicit assumptions that the firm, somehow, performs these spesific actions better than the others do.
The marketing strategies in small business: A case of food industry
Keywords: Ma; markkinointistrategiat; pienyritykset; elintarvikkeiden markkinointi; marketing strategy; positioning; goal setting; food industry